Study on the Anthropology of Syriac Church Father Mar Jacob of Sarug - DUAN, Wenjunyi (Journal of Research for Christianity in China (JRCC), 2024)
Mar Jacob of Sarug is an important Syriac church father. This article takes the homily 71 “The Six Days of Creation” and the homily 72 “On the Creation of Adam and the Resurrection of the Dead” and other Mar Jacob’s homilies as the starting point to conduct a discussion on his anthropology. Firstly, Mar Jacob calls the world created by God a beautiful world, and humankind is the most beautiful creature. Secondly, Mar Jacob believed that humankind is the image of God—humankind is different from other creatures in the way of creation, and was created by God according to his image and likeness, “to the Father, Adam will be the image; to the Son, Adam will be the likeness”. In his view, the nous or intellect of humankind is similar to God himself, while human soul is similar to the power of God, and human body to the material world which consists of four elements and six directions. Therefore, humankind is a “small world” that reflects God and the “great world” which He created. This very beautiful creature, this “small world” is disintegrating due to the temptation of the Satan and man's free will, but Mar Jacob points out that through God's salvation, humankind will regain beauty and clothe on light, through the “second creation” on the resurrection.
Keywords: Anthropology; Jacob of Sarug; Oriental Church Father; Syriac Church